2022
DOI: 10.3390/su142114080
|View full text |Cite
|
Sign up to set email alerts
|

Response of Water Yield to Future Climate Change Based on InVEST and CMIP6—A Case Study of the Chaohu Lake Basin

Abstract: The Chaohu Lake Basin (CLB) is the main flow area of the Yangtze River–Huaihe River Water Transfer Project in Central China. It is important to quantitatively evaluate the water resources in the CLB and predict their response to future climate change. This study simulated and calibrated the water yield in the CLB from 2000 to 2019 based on InVEST. We also analyzed the influence factor on the water yield and predicted the water yield in future years with CMIP6 data. The results demonstrate that: (1) The InVEST … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 47 publications
0
1
0
Order By: Relevance
“…It was concluded that the spatial variability of the natural environment has a greater impact on ecosystems than temporal fluctuations [6][7][8][9]. In China, research on land-water interface zones is focused on Dongting Lake [10], Chaohu Lake [11], Poyang Lake [12], and other important water bodies. The basic characteristics of the landscape pattern changes in the relevant study areas were explored; the landscape changes of different characteristics reflect different land use conditions, and the means and extent of the impact of human activities on the value of ecosystem services were revealed through land use.…”
Section: Introductionmentioning
confidence: 99%
“…It was concluded that the spatial variability of the natural environment has a greater impact on ecosystems than temporal fluctuations [6][7][8][9]. In China, research on land-water interface zones is focused on Dongting Lake [10], Chaohu Lake [11], Poyang Lake [12], and other important water bodies. The basic characteristics of the landscape pattern changes in the relevant study areas were explored; the landscape changes of different characteristics reflect different land use conditions, and the means and extent of the impact of human activities on the value of ecosystem services were revealed through land use.…”
Section: Introductionmentioning
confidence: 99%